2020
DOI: 10.3389/fvets.2020.00154
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Spatial and Temporal Patterns of African Swine Fever in an Isolated Wild Boar Population to Support Decision-Making

Abstract: African swine fever (ASF) is a highly contagious disease affecting all suids including wild boar. As the disease can damage commercial pig production and its circulation can threaten international trade, understanding the risks produced by free-living wild boar (as a wildlife reservoir) is important to ensure proportionate policies to exclude the disease, as well as an effective contingency response. The recent spread of the virus into Western Europe has produced concerns in many stakeholders including pig pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Nevertheless, transmission of the disease in domestic pig farms in the Baltic countries and Poland was related mainly to the epidemic occurring in the wild boar population, the wild boar habitat suitability, and the neighbouring distance from infected wild boars and domestic pigs [ 15 , 67 ]. On the contrary, Croft et al [ 68 ] developed a model to evaluate the possible introduction and spread of ASFV in a wild boar population in England, and their results suggested a relationship between animal density and the rate of disease spread and that the extent of the wildlife–host distribution could be an important factor predicting the duration of an outbreak. Pautenius et al [ 69 ], after studying the spatiotemporal distribution of ASF outbreaks in Lithuania, concluded that there is no correlation between the population density of wild boars and ASFV prevalence in a given region but that it might have an effect on the risk of ASFV introduction into another wild boar population in the case of an increased dispersal distance of adult males.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, transmission of the disease in domestic pig farms in the Baltic countries and Poland was related mainly to the epidemic occurring in the wild boar population, the wild boar habitat suitability, and the neighbouring distance from infected wild boars and domestic pigs [ 15 , 67 ]. On the contrary, Croft et al [ 68 ] developed a model to evaluate the possible introduction and spread of ASFV in a wild boar population in England, and their results suggested a relationship between animal density and the rate of disease spread and that the extent of the wildlife–host distribution could be an important factor predicting the duration of an outbreak. Pautenius et al [ 69 ], after studying the spatiotemporal distribution of ASF outbreaks in Lithuania, concluded that there is no correlation between the population density of wild boars and ASFV prevalence in a given region but that it might have an effect on the risk of ASFV introduction into another wild boar population in the case of an increased dispersal distance of adult males.…”
Section: Resultsmentioning
confidence: 99%
“…0.1 animal/ km 2 ) wild boar density, and there is no evidence of a population threshold for spontaneous ASF fadeout (EFSA AHW Panel, 2018). Croft et al (2020) suggest that reduction in outbreak severity is influenced by wild boar distribution rather than density or overall population size. Bosch et al (2016) came to similar conclusions, but in a different context, suggesting that wild boar presence was a more important indicator than wild boar density for the risk of ASF introduction.…”
Section: Factors Relating To Wild Boar Ecological and Demographic Facmentioning
confidence: 99%
“…Croft et al. (2020) suggest that reduction in outbreak severity is influenced by wild boar distribution rather than density or overall population size. Bosch et al.…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Another model combined the habitat suitability with an agent-based, spatially explicit simulation model that includes multi-source citizen science data on the presence of wild boar [ 171 ]. Croft et al (2020) used a spatial individual-based model with data of a real landscape area in Britain for an isolated wild boar population [ 172 ].…”
Section: Epidemiologymentioning
confidence: 99%